Pemilihan Saham yang Optimal Menggunakan Capital Asset Pricing Model (CAPM) - Dioda Ardi Wibisono; Krisnawuri Handayani (Jurnal Manajemen dan Kewirausahaan, 2017)
Optimal portfolio is the basis for investors to invest in stock. Capital Asset Pricing Model (CAPM) is a method to determine the value of the risk and return of a company stock. This research used are secondary data from the closing price of the monthly stock price (monthly closing price), Stock Price Index (SPI), and the monthly SBI rate. Samples taken as many as 41 stocks in LQ45 February-July 2015 on the Indonesian Stock Exchange (ISE). The study period during 5 year from October 2010 - October 2015. The result of analysis shows that the optimal portfolio consists of 18 companie. The average return of the optimal portfolio is higher than the average risk-free return (SBI rate) and the average market return. This proves that investing in stocks is more profitable than a risk-free investment.   https://doi.org/10.26905/jmdk.v5i1.1315